PENGARUH KEPEMILIKAN INSTITUSIONAL, TRANSFER PRICING, DAN FAKTOR LAINNYA TERHADAP PENGHINDARAN PAJAK - Dinda Arliani; Yohanes (E-Jurnal Akuntansi TSM, 2023)
The purpose of the study is to obtain empirical evidence of the effect of institutional ownership, transfer pricing, sales growth, company size, return on assets, and leverage on tax avoidance. The population of this study is manufacturing companies listed on the Indonesia Stock Exchange during 2019 to 2021. Sample selection uses the purposive sampling method with a total of 240 companies and a total sample data of 80 companies. This study used the method of multiple regression data analysis. Empirical evidence obtained from this study shows that leverage has an influence on tax avoidance, while institutional ownership, transfer pricing, sales growth, company size, and return on assets have no influence on tax avoidance. Companies financing their operational activities using large amounts of debt will cause the company's tax burden to become higher, so the company tends not to carry out tax avoidance practices.